MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA SISWA KELAS V MELALUI METODE PEMBELAJARAN KOOPERATIF PADA MATERI SISTEM PEREDARAN DARAH MANUSIA DI SD NEGERI 15 BANDA ACEH - Alya, Mughni; Kasmini, Lili; Sari, Siti Mayang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve the critical thinking skills of fifth grade students through the application of cooperative learning methods to material on the human circulatory system at State Elementary School 15 Banda Aceh. The research method used was descriptive qualitative, with research subjects consisting of all class V students and class V teachers. Data was collected through observation and structured interviews to understand the implementation of learning methods. The research results show that the application of cooperative methods is effective in encouraging students' active participation in discussions, supporting each other, and increasing collaboration. Students are more enthusiastic and responsible for the results of group work, and are able to analyze and apply the concepts learned in the context of everyday life. Despite the challenges of managing group dynamics, strategies such as role assignment and constructive feedback succeeded in creating a positive learning atmosphere. These findings suggest that cooperative learning methods not only contribute to academic understanding, but also to the development of important social skills for students. It is hoped that this research can become a reference for teachers in implementing effective learning methods to improve the quality of education in the future.